2012
DOI: 10.1210/en.2012-1287
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin B and the Control of the Gonadotropic Axis in the Rat: Developmental Changes, Sexual Dimorphism, and Regulation by Gonadal Steroids

Abstract: Neurokinin B (NKB), encoded by Tac2 in rodents, and its receptor, NK3R, have recently emerged as important regulators of reproduction; NKB has been proposed to stimulate kisspeptin output onto GnRH neurons. Accordingly, NKB has been shown to induce gonadotropin release in several species; yet, null or even inhibitory effects of NKB have been also reported. The basis for these discrepant findings, as well as other key aspects of NKB function, remains unknown. We report here that in the rat, LH responses to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 44 publications
5
63
1
1
Order By: Relevance
“…Considering the relevant role of NKB signaling in the central control of the reproductive axis, the involvement of NKB in the onset of puberty has begun to be evaluated recently; yet, the number of studies on this particular area remains scarce (39,41,42). Notwithstanding, our data on immature rats demonstrate that, like adult, cyclic females, prepubertal female rats are able to respond to the NKB agonist, senktide, with robust LH responses (41).…”
Section: Kisspeptins: Major Gatekeepers Of Pubertymentioning
confidence: 73%
See 2 more Smart Citations
“…Considering the relevant role of NKB signaling in the central control of the reproductive axis, the involvement of NKB in the onset of puberty has begun to be evaluated recently; yet, the number of studies on this particular area remains scarce (39,41,42). Notwithstanding, our data on immature rats demonstrate that, like adult, cyclic females, prepubertal female rats are able to respond to the NKB agonist, senktide, with robust LH responses (41).…”
Section: Kisspeptins: Major Gatekeepers Of Pubertymentioning
confidence: 73%
“…The basis for these discrepant observations remains partially unknown, but they may stem from differences in the age, sex, species, and prevailing gonadotropin levels. Indeed, evidence for inhibitory effects of senktide on LH secretion comes mostly from animal models with pre-elevated LH concentrations, namely gonadectomy (GNX) without adequate sex steroid replacement (37,38,39). In this context, proof of desensitization of NKB-induced LH responses has been presented in the monkey (28).…”
Section: Kisspeptins: Major Gatekeepers Of Pubertymentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, in our experiments, senktide did not modify basal LH or FSH levels in young adult male rats, an observation that is in contrast to the potent stimulatory effects of this agonist on gonadotropin secretion in adult male mice (12,32). However, the possibility of an experimental artifact can be discarded since parallel studies, using strictly similar peptide preparations and experimental conditions, revealed potent stimulatory effects of senktide on LH secretion in female rats at various developmental stages (30), as well as in male rats, during the infantile and prepubertal period (48). Moreover, despite the inability to modify basal gonadotropin levels, preactivation of NKB signaling significantly attenuated LH and FSH responses to Kp-10.…”
Section: Kisspeptin-neuropeptidergic Interactions In the Control Of Gmentioning
confidence: 99%
“…Collectively, these and related findings have led to the hypothesis that NKB (auto)regulates Kp output from ARC Kiss1 neurons onto GnRH neurons (33,34,53). However, stimulatory, inhibitory, or null effects of the agonist of NKB, senktide, on LH secretion have been reported, depending on the sex steroid milieu and the functional state of the gonadotropic axis (5,22,30,32,42,43,48,51), a phenomenon whose basis remains unknown. Moreover, the ability of NKB to modulate GnRH/gonadotropin responses to Kp remains unexplored.…”
mentioning
confidence: 99%